Evaluation of a novel technique for screening cowpea varieties for resistance to the seed beetle Callosobruchus maculatus - Deverau, A.D.; Jackai, L.E.N.; Olusegun, T.B.; Asiwe, A.N.J. (2002)
A novel method for screening cowpea varieties for resistance to the postharvest insect pest Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) was compared to conventional screening techniques at the International Institute for Tropical Agriculture (IITA) laboratory in Ibadan, Nigeria. The new technique assesses seed resistance by measuring larval feeding activity via electronic sensors. Initial smallscale trials demonstrated that the method could be successfully applied in the laboratory with a potential saving in time and effort. The results were used to design a larger scale device that was able to screen 32 varieties of cowpea in 1 9 days using a methodology designed to identify only the most resistant cowpea varieties. Resistant varieties were identified but some problems were encountered with analysis of the results. Practical application of the technique for large-scale resis tance screening is discussed.